2018
DOI: 10.2169/internalmedicine.1121-18
|View full text |Cite
|
Sign up to set email alerts
|

Anti-MDA5 Antibody-positive Dermatomyositis Complicated by Autoimmune-associated Hemophagocytic Syndrome That Was Successfully Treated with Immunosuppressive Therapy and Plasmapheresis

Abstract: A 56-year-old Japanese woman with muscle weakness, increased creatine kinase and aldolase levels, and characteristic cutaneous lesions was diagnosed with anti-melanoma differentiation-associated gene 5 antibody (anti-MDA5 antibody)-positive dermatomyositis. She also had interstitial lung disease (ILD). After corticosteroid and tacrolimus combination therapy was started, bicytopenia and elevated serum ferritin and transaminase emerged. Because the bone marrow tissues were hypoplastic with hemophagocytes, she wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…Previously, a randomized controlled trial showed no effect of plasmapheresis on polymyositis or DM, but the enrolled patients were heterogeneous and the trial end points were measurements of muscle disease activity . Notably, recent case reports have indicated the efficacy of plasmapheresis in patients with anti–MDA‐5–positive rapidly progressive ILD . Polymyxin B–immobilized fiber column direct hemoperfusion has also been suggested as potentially effective for ILD in CADM or anti–MDA‐5–positive rapidly progressive ILD , although the effect was controversial .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, a randomized controlled trial showed no effect of plasmapheresis on polymyositis or DM, but the enrolled patients were heterogeneous and the trial end points were measurements of muscle disease activity . Notably, recent case reports have indicated the efficacy of plasmapheresis in patients with anti–MDA‐5–positive rapidly progressive ILD . Polymyxin B–immobilized fiber column direct hemoperfusion has also been suggested as potentially effective for ILD in CADM or anti–MDA‐5–positive rapidly progressive ILD , although the effect was controversial .…”
Section: Discussionmentioning
confidence: 99%
“…CyA or tacrolimus with or without intravenous immunoglobulins (IVIG) is a mainstay of pharmacologic treatment of the anti-MDA5 syndrome [49]. In addition, cases of anti-MDA5 syndrome complicated by haemophagocytic syndrome have been described [50]. Thus, according to the antiviral and anti-inflammatory properties of calcineurin inhibitors, CyA and tacrolimus could be potential effective drugs for treating the severe forms of COVID-19.…”
Section: Interleukin-2 Inhibitionmentioning
confidence: 99%
“…IV immunoglobulin (IVIG) is beneficial in active muscle disease, although efficacy for ILD specifically remains unclear 151 . Plasmapheresis is generally reserved for severe multiorgan disease, although evidence for its role specifically in IIM‐ILD is limited 152–154 . Due to the risk of worsening or relapsed ILD, immunosuppression is generally maintained for a relatively long duration (often >2–5 years), although controlled treatment data are lacking.…”
Section: Specific Ctd‐ildmentioning
confidence: 99%